THE CONTRIBUTION OF CULTURAL FACTORS IN THE UTILIZATION OF MATERNAL HEALTH SERVICES AMONG WOMEN IN AMUDAT SUB-COUNTY AMUDAT DISTRICT. - KIYONGA NANCY (My University, 2024)
ABSTRACT This research report entitled "The Contribution of cultural factors in the utilization of maternal health services among women in Amudat sub-county Amudat district", it was guided by the following research objectives; To dentify the social cultural factors hindering the utilization of maternal health services in Amudat sub-county in Amudat district, to examine the social factors surrounding the environment affects the utilization of maternal health services in Amudat sub-county Amudat district, and lastlyto develop interventions that are culturally sensitive and effective in improving maternal health outcomes for women in the community of Amudat sub county, Amudat district. The research also focused on the following questions; What are the social cultural factors hindering the utilization of maternal health services in Amudat sub-County, Amudat district?, What are the factors surrounding the environment that affects the utilization of maternal health services in Amudat sub-county Amudat district?, What are the interventions that are culturally sensitive and effective in improving maternal health outcomes for women in the community of Amudat sub-county, Amudat district.? The sample size of the study was (n=80). Where by (30) respondents were interviewed while fifty (50) participants filled up questionnaires. Qualitative data analysis involved the presentation of data inform of text or words, stories, quotations, opinions and group discussions. Quantitative data was analysed statistically. The research study findings showed that, social cultural factors including preferences for traditional birth attendants, gender roles and lack of education were the factors hindering the utilization of maternal health services in Amudat sub-county, in the women also are affected due to lack of freedom to decisions making, the long distances to health facilities, conflicts and migrations makes them have unsettled lifestyle, it was also found out that negative Attitudes and cultural beliefs about the health services affects the utilization of maternal health services. The research recommended the following;